Differential effect of NDGA on cisplatin-induced nephrotoxicity in Spargue-Dawley rats. (2nd January 2019) - Mundhe, Nitin; Kumar, Parveen; Arora, Ishan; Ahmed, Sahabuddin; Lahkar, Mangala
Abstract: Context: Nephrotoxicity is a highly manifested complication in cancer patients undergoing cisplatin therapy. Oxidative stress, nitrosative stress, and inflammation are the major patho-mechanisms of cisplatin-induced nephrotoxicity. Objective: The purpose of this study was to determine the protective effect of pretreatment and post-treatment of nordihydroguaiarectic acid (NDGA) on cisplatin-induced nephrotoxicity. Material and methods: Cisplatin-induced renal damage was accessed by biochemical estimation of nephrotoxicity markers, oxidative and nitrosative stress whereas inflammatory markers were accessed by ELISA technique. Results and conclusion: Cisplatin administration had resulted in renal injury associated with oxidative stress, nitrosative stress as evident by increased MDA, ROS, and nitrite level with decreased antioxidants such as SOD, catalase and, glutathione. Furthermore, cisplatin treated animals exhibited a noticeable pro-inflammatory response with the substantial increase in renal levels of TNF-α, IL-1β, and IL-6 and decrease in the renal level of IL-10. NDGA pretreatment did not lead to significantly rise in oxidative stress, nitrosative stress, and inflammation along with restored the level of IL-10 in the kidney and preserved renal function. Moreover, NDGA post-treatment also presented nephroprotective effects, but the effects were not as positive as compared to NDGA pretreatment. In conclusion, these results indicate that NDGA pretreatment is renoprotective while on the other hand NDGA post-treatment is not so effective in cisplatin-induced nephrotoxicity.